SANITATION AND DETOXIFICATION OF ALPACA MEAT (VICUGNA PACOS) WITH SARCOCYSTOSIS BY PHYSICAL AND CHEMICAL METHODS OF HOME USE - Céspedes V., Cristhian (2013)
Physical and chemical methods of home use techniques for sanitation and detoxification of alpaca meat infected with macrocysts of Sarcocystis aucheniae were evaluated. The physical treatments were boiling and baking at 80 °C for 5 minutes and freezing for 10, 15 and 20 days; and the chemical treatments were salting for 15 and 30 days, and marinated for 24 hours. Dogs were fed with bouts of treated alpaca meat containing 180-200 macrocysts and the presence of oocysts were analyzed in faeces for 18 days. Besides, macrocysts lisates were injected to rabbits to evaluate the detoxifying effect of treatments on the protein content of the macrocysts. Only the physical treatments proved to be effective in sanitizing alpaca infected meat, whereas the toxin biological activity could not be altered.